Etika Protestan dan Asketisme dalam Pemikiran Max Weber - Endrika Widdia Putri (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The use of social media to transform positive values among the younger generation and millennials, including the values of religious tolerance, is very significant to do in the current era of information technology. Relevant to that, this study aims to explore messages of religious tolerance found on social media, in this case the vlog belongs to Gita Savitri Devi, a youtuber and social media activist. This research is a qualitative type of library research, because the data collected is obtained from library materials, especially video documentation from Gita's YouTube. The data were analyzed using content analysis techniques. The results obtained are that in Gita Safitri Devi's vlog, especially the seven video shows, there are five elements of religious tolerance including, acknowledging the rights of others, respecting other people's beliefs, agreeing in disagreement, understanding each other, as well as awareness and honesty. It can be concluded that Gita Savitri Devi through her vlog seeks to participate in transforming the values of religious tolerance to young people, especially millennials who love social media.Artikel ini bertujuan untuk menganalisis pandangan Max Weber (1864–1920) sosiolog modern asal Jerman mengenai kaitan antara etika Protestan dan asketisme. Di mana artikel ini menggunakan metode eksploratif dan analitis kritis untuk mendapatkan hasil yang dicari. Hasil studi menemukan bahwa asketisme dalam pandangan Max Weber yang terdapat dalam etika Protestan adalah pengendalian diri dalam kehidupan duniawi dengan tujuan mendapatkan jaminan surga dari Tuhan, dengan melakukan berbagai kewajiban moral, seperti; berbuat baik, hidup sederhana; tidak berlebihan dan tidak berkekurangan, semangat bekerja memperoleh materi dan hidup sopan santun serta saling menolong. Dalam pandangan Max Weber terdapat hubungan timbal balik yang saling menstimulus antara asketisme yang ada dalam etika Protestan dan kapitalisme. Bahwa untuk mendapatkan calling Tuhan manusia harus bekerja keras di dunia, namun tanpa meninggalkan pola hidup asketis; hemat, tidak berfoya-foya, tidak berlebihan dan lain sebagainya yang mengambarkan kebaikan moral.